A Paradox of Student Bullying Prevention in China: Between Social Anxiety and the Reaction to it - Gui Huang (Faculty of Law, Hasanuddin University, 2022)
Student bullying has been considered a serious social problem. This is because, firstly, student bullying cases have been occurring frequently in recent years, and have raised many guardians’ concerns for their child’s safety and healthy growth; secondly, the school and the government aren’t able to take effective measures to prevent student bullying. The reasons behind it vary, but the family dynamic— failing to cultivate a wholesome personality in the child, lacking of guardian supervision and family education, and the school climate—the boarding school system and bureaucratic formalism in school—are the two key ones. In these two years, the authorities have improved measures by adopting and amending Law on the Protection of Minors and administrative regulations, including Regulation on the School Protection of Juvenile, Directive on Preventing and Governing Student Bullying and Violence in Primary and High Schools, with the aim of eliminating the formalism and bureaucratism.